Characteristic Biomarker and Cognitive Profile in Incipient Mixed Dementia - Eckerström, Carl (J Alzheimers Dis, 2020)
BACKGROUND: Research has shown that mixed dementia is more common than previously believed but little is known of its early stages. OBJECTIVE: To examine if incipient mixed dementia can be differentiated from incipient Alzheimer’s disease (AD) and subcortical ischemic vascular dementia (SVD) using neuropsychological tests, cerebrospinal fluid (CSF) markers, and magnetic resonance imaging markers. METHODS: We included 493 patients and controls from the Gothenburg MCI study and used the dementia groups for marker selection (CSF total-tau (T-tau), phospho-tau (P-tau), and amyloid-β(42) (Aβ(42)), 11 neuropsychological tests, and 92 regional brain volumes) and to obtain cut-off values which were then applied to the MCI groups. RESULTS: Incipient mixed dementia was best differentiated from incipient AD by the Word fluency F-A-S test and the Trail making test A. CSF T-tau, P-tau, and Aβ(42) differentiated incipient mixed dementia from incipient SVD. CONCLUSION: Incipient mixed dementia is characterized by an AD-like biomarker profile and an SVD-like cognitive profile. Incipient mixed dementia can be separated from incipient AD and incipient SVD using CSF markers and cognitive testing.